Professional Interests in the Early Youth: Peculiarities of Boys and Girls - Kasyanova, T; Maltsev, A; Zubova, L (KnE Life Sciences, 2018)
We give the results of research interests in choosing a profession among high school students. The sample consisted of 859 people, 385 of them were boys and 474 were girls between the ages of 14 and 18. The purpose of the study is to study the differences in interests between young men and women that we identified earlier in the professional fields of technology and art in relation to other professional spheres. For the study, the results of computer testing, using the ‘Proforientator’ method, were used. Studies have made it possible to identify the psychological construct as a community of interests in the professional fields of technology, science and sign. Another distinguished psychological construct is the combination of interests of art, communication, business and sign. It is shown that there are specific, reflecting gender identity in addition to the common interests in the professional socialization among boys and girls. The following specific features are revealed: interest in technology among young men is an additional combination with interests in the professions of business and art. So, girls have an additional combination of interests in the fields of nature and communication but young men have interest in art and it is combined with interests in the professions of science and nature. Keywords: interests, professional socialization, professional spheres, career guidance work with teenagers